Pengaruh Penggunaan Model Pembelajaran dan Konsep Diri terhadap Kemampuan Berpikir Kretif Mahasiswa - Nurul Hikmah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2013)
The purpose of this study were to determine: 1) the influence of the learning model of creative thinking; 2) the influence of self-concept to think creatively, and 3) the influence of the interaction and the concept of self-learning model for creative thinking. The research method used was experimental method. A sample of 80 people selected at random from the 13 study groups. The data was collected by administering a written test questions to measure variables studied. Data analysis using descriptive statistics and 2-way ANOVA. The results showed: 1) a significant difference to the learning model with the ability to think creatively sig = 0.000; 2) there is a significant effect of self-concept of the ability to think creatively with sig = 0.000, and 3) there is a significant interaction effect of learning model and self-concept of the ability to think creatively with sig = 0.018.